Effects of extraction, storage conditions and heating treatment on antibacterial activity of zanthoxylum fagara honey from Cojedes, Venezuela - Ríos, Agustina Manuela; Novoa, María Luisa; Vit, Patricia (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
In this study, the influence of extraction, storage conditions and heating treatment on the antibacterial activity of Zanthoxylum fagara honey produced by Apis mellifera was researched. For that purpose, scraped and centrifuged honey samples from the Guilan apiaries (Cojedes state, Venezuela) were stored in darkness or sunlight for four months and exposed to different heat treatments (40°C for 30 days, and 78°C for 5, 10 and 15 min). The antibacterial activity was studied for 5%, 10%, 15%, 20% and 25% of bees honey in nutrient agar and the inhibitory grade was ranked from 0 to 5. The selected bacterial strains for this study were Bacillus subtilis, Escherichia coli, Listeria spp., Pseudomonas aeruginosa and Staphylococcus aureus. Storage in darkness or sunlight for four months, as well as mild heat treatment (40°C for 30 days) did not affect the antibacterial properties. Antibacterial activity was higher in scraped honey, but it was more vulnerable to heat treatment than centrifuged honey. Exposures of scraped honeys at 78°C for 15 minutes significantly decreased the antibacterial activity, with partial losses of 67, 4% for E. coli and 54% for S. aureus. Listeria spp. was the most sensitive bacteria. E. coli was the most resistant bacteria for heated honey and B. subtilis the most resistant for fresh honey.